Expression Analysis of ATP-Binding Cassette Transporters ABCB11 and ABCB4 in Primary Sclerosing Cholangitis and Variety of Pediatric and Adult Cholestatic and Noncholestatic Liver Diseases. (10th December 2019) - Thoeni, Cornelia; Waldherr, Ruediger; Scheuerer, Jutta; Schmitteckert, Stefanie; Roeth, Ralph; Niesler, Beate; Cutz, Ernest; Flechtenmacher, Christa; Goeppert, Benjamin; Schirmacher, Peter; Lasitschka, Felix
Abstract : ATP-binding cassette (ABC) transporters are the members of the efflux pumps that are responsible for the removal of cytotoxic substances by active transport. ABCB11, the bile salt efflux pump of hepatocytes, coordinates cellular excretion of numerous conjugated bile salts into the bile canaliculi, whereas ABCB4 acts as an ATP-dependent floppase translocating phosphatidylcholine from the inner to the outer leaflet of the bile canalicular membrane. Loss of functional ABCB11 and ABCB4 proteins causes early-onset refractory cholestasis or cholangiopathy. In this study, we investigated the expression and localization pattern of ABCB11 and ABCB4 using immunohistochemistry and RNA profiling in liver samples from patients with different types and stages of chronic cholestatic liver disease, with emphasis on primary sclerosing cholangitis (PSC), compared to a variety of cholestatic and noncholestatic hepatopathies. Therefore, ABCB11 and ABCB4 expressions were investigated on formalin-fixed and paraffin-embedded (FFPE) material in a patient cohort of total 43 patients with or without cholestatic liver diseases, on protein level using immunohistochemistry and on RNA level using nanoString technology. Intriguingly, our results demonstrated increased expression of ABCB11 and ABCB4 on protein as well as RNA level in PSC, and the expression pattern correlated with disease progression. We concluded from our study that patients with PSC demonstrate altered expression levels and pattern of ABCB11 and ABCB4 which correlated with disease progression; thereby, ABCB11 and ABCB4 analysis may be a useful tool for assessment of disease stages in PSC.